2007
DOI: 10.1113/jphysiol.2006.119594
|View full text |Cite
|
Sign up to set email alerts
|

Brainstem PCO2 modulates phrenic responses to specific carotid body hypoxia in an in situ dual perfused rat preparation

Abstract: Inputs from central (brainstem) and peripheral (carotid body) respiratory chemoreceptors are coordinated to protect blood gases against potentially deleterious fluctuations. However, the mathematics of the steady-state interaction between chemoreceptors has been difficult to ascertain. Further, how this interaction affects time-dependent phenomena (in which chemoresponses depend upon previous experience) is largely unknown. To determine how central P CO 2 modulates the response to peripheral chemostimulation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
67
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(87 citation statements)
references
References 72 publications
17
67
3
Order By: Relevance
“…While this specific hypothesis remains to be tested, an interaction between central and peripheral chemoreflexes has already been demonstrated by several other investigators. It has been found that central hypocapnia, or alkalosis, results in an augmented respiratory response to peripheral chemoreceptor stimulation (5,17,66). In other words, when hypoxia is accompanied by central hypocapnia, ventilation is greater than it is when central isocapnia is maintained.…”
Section: Discussionmentioning
confidence: 96%
“…While this specific hypothesis remains to be tested, an interaction between central and peripheral chemoreflexes has already been demonstrated by several other investigators. It has been found that central hypocapnia, or alkalosis, results in an augmented respiratory response to peripheral chemoreceptor stimulation (5,17,66). In other words, when hypoxia is accompanied by central hypocapnia, ventilation is greater than it is when central isocapnia is maintained.…”
Section: Discussionmentioning
confidence: 96%
“…Nevertheless, these data suggest that results obtained in isolated organs, such as the in vitro carotid body preparation may not always apply to the ventilatory response observed at the whole animal level. There is growing evidence indicating that peripheral and central chemoreceptors are interdependent, such that the sensitivity of the medullary chemoreceptors is highly determined by input from carotid bodies and perhaps by other sensory afferents (4,10,11,57). Although difficult to explain and reconcile with current knowledge, one must keep in mind that the nature of the interdependence between central and peripheral chemoreceptors remains controversial as various types of interactions (e.g., hypoadditive and hyperadditive) have been reported, owing, in part, to differences in experimental approaches used (57).…”
Section: Neonatal Stress and Its Consequences On Pa O 2 Modulation Ofmentioning
confidence: 99%
“…On the basis of indirect evidence indicating that NMS augments carotid body's responsiveness to hypoxia (35,36), it was proposed that the relative hyperoxia that occurs during hypercapnic hyperpnea [ϳ20 mmHg increase (34)] is sufficient to attenuate the CO 2 response of NMS rats (21). However, the recent evidence indicating that central and peripheral chemoreceptors are interdependent and influence each other's sensitivity (4,10,11,57) raises the possibility that NMS disrupts this interaction.…”
mentioning
confidence: 99%
“…Ventilatory movements are delivered by respiratory central pattern generators (rCPGs) distributed bilaterally in the pons and ventral medulla. These semiautonomous neural networks comprise core circuits of excitatory and inhibitory interneurons that deliver rhythmic patterns of activity (10) and confer a set point about which respiratory rhythm is continuously modulated through the integration of inputs from those central (10,11) and peripheral (12) chemosensors that monitor O 2 , CO 2 , and pH. It is generally accepted that the carotid bodies represent the primary arterial chemoreceptors (12) and that the acute hypoxic ventilatory response (HVR) is delivered by increased afferent discharge from the carotid bodies to the rCPGs via, in great part, catecholaminergic networks within the caudal brainstem (13,14).…”
mentioning
confidence: 99%